Granulomatous peritonitis caused by iatrogenic spillage of ovarian dermoid cystectomy: a case report and literature review - Hyo-Eun Kim; Minji Seo; Jae Young Kwack; Yong-Soon Kwon (Korean Society of Obstetrics and Gynecology, 2020)
A 39-year-old nulliparous woman experienced continuous mild fever and abdominal pain since undergoing laparoscopic ovarian dermoid cystectomy 3 months previously in a local hospital. Abdominal computed tomography revealed diffuse heterogeneous fat infiltrations with numerous micronodules in the greater and lesser omentum, combined with ascites with thickening of the parietal peritoneum. The patient underwent exploratory laparoscopy, which included partial pelvic peritonectomy, excision of granulomas, and adhesiolysis with massive irrigation. The patient was treated successfully with laparoscopic surgery and all reproductive structures were spared without operative complications. To avoid peritonitis, complete removal of cyst contents and massive irrigation should be performed during ovarian dermoid cystectomy. Conservative surgical treatment may be a good choice for treating granulomatous peritonitis induced by iatrogenic rupture.